2022
DOI: 10.1136/jnis-2022-019556
|View full text |Cite
|
Sign up to set email alerts
|

Simplified stroke imaging selection modality for endovascular thrombectomy in the extended time window: systematic review and meta-analysis

Abstract: BackgroundThe impact of imaging selection modality on clinical outcomes of endovascular thrombectomy (EVT) in the 6–24-hour time window remains undetermined. We compared the clinical outcomes of a simplified stroke imaging selection modality using non-contrast computed tomography (NCCT)±CT angiography (CTA) with using advanced CT perfusion (CTP).MethodsPubMed, Embase, Web of Science, and Cochrane Central Register of Controlled Trials were searched from inception to 1 May 2022 to compare NCCT±CTA and CTP for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…16 The very poor natural history of anterior circulation large vessel occlusion also indicates to us a great potential benefit of thrombectomy based even on simple, pragmatic criteria like baseline NIHSS ≥ 6 and baseline non-contrast CT scans (ASPECTS ≥ 5). 13 In the present study, which sought to precisely assess the outcomes of thrombectomy in the late time window under pragmatic criteria, we included in the analysis only patients treated in a known late time window (> 6 hours), with NIHSS ≥ 6 and ASPECTS ≥ 5. The control group comprised patients presenting with the same characteristics but treated within the standard early time window.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 The very poor natural history of anterior circulation large vessel occlusion also indicates to us a great potential benefit of thrombectomy based even on simple, pragmatic criteria like baseline NIHSS ≥ 6 and baseline non-contrast CT scans (ASPECTS ≥ 5). 13 In the present study, which sought to precisely assess the outcomes of thrombectomy in the late time window under pragmatic criteria, we included in the analysis only patients treated in a known late time window (> 6 hours), with NIHSS ≥ 6 and ASPECTS ≥ 5. The control group comprised patients presenting with the same characteristics but treated within the standard early time window.…”
Section: Discussionmentioning
confidence: 99%
“…16 The very poor natural history of anterior circulation large vessel occlusion also indicates to us a great potential benefit of thrombectomy based even on simple, pragmatic criteria like baseline NIHSS ≥ 6 and baseline non-contrast CT scans (ASPECTS ≥ 5). 13…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a recent large retrospective observational study, CLEAR, found that ELVIS patients undergoing EVT utilizing non-perfusion CT imaging for decision-making had comparable clinical outcomes compared to those that utilized perfusion CT or magnetic resonance imaging [ 18 ]. Systematic reviews comparing outcomes between late-window ELVIS patients who obtain non-perfusion CT and perfusion CT prior to undergoing EVT do not show a significant difference in benefit in terms of clinical outcomes [ 19 , 20 ]. However, these reviews are all based on observational data from large databases.…”
Section: Introductionmentioning
confidence: 99%